Making Dictionary Content Accessible for People with Visual Impairments - Rees, Geraint Paul (Lexikos, 2025)
This article discusses the development and evaluation of EDictViz: a visually accessible dictionary website intended to meet the accessibility needs of people with visual impairments. It is argued that dictionary access is important not only because of the utilitarian role that dictionaries play in resolving language queries but also because of their potential to promote social inclusion. With reference to previous research, a summary is provided of the barriers to access typically faced by people with visual impairments when using dictionary websites. Following this, the way in which these problems have been addressed in the development and evaluation process of EDictViz thus far is discussed. An evaluation of a development version of EDictViz based on the Web Content Accessibility Guidelines is reported — it indicates that the latest prototype version of the tool is accessible. This suggests that the design decisions taken at the outset of the project were sound. Throughout this process the parallels between lexicography research, which is often concerned with providing efficient access to lexicographic data, and accessibility research in general are drawn. Plans for future experimental studies to evaluate EDictViz which directly involve people with visual impairments are set out. This development process demonstrates the potential for mutually beneficial collaboration between accessibility and lexicography researchers. Keywords: accessibility, advertisements, education, language learning, language teaching, lexicography, lexicotainment, online dictionaries, WCAG, web development